Review: Leptospirosis in Dogs in Indonesia - Wiyata, Rifen Prabawan Krida Taruna; Nugroho, Widi (Veterinary Biomedical and Clinical Journal, 2021)
Leptospirosis is an infectious disease caused by motile bacteria of the genus Leptospira. The prevalence of leptospirosis in dogs in Indonesia ranges from 13,8% - 44%, with Leptospira variants including the serovars Ichterohaemorragiae, Celledoni, Canicola, Pyrogenes, Cynopteri, Rachmati, Bataviae, Javanica, Grippotyphosa and Tarrasovi. Leptospira sp. can be transmitted through direct contact with an infected animal, soil or water contaminated with Leptospira sp. Rodents, pigs, horses, farm animals, dogs and various wild animals such as squirrels and deer can serve as carriers of Leptospira sp. Clinical symptoms of leptospirosis in dogs in Indonesia include fever, lethargy, anorexia, vomiting, jaundice, kidney disorders, dyspnea, polyuria, yellow urine, dehydration and death. The gold standard for leptospirosis testing in dogs is the MAT test, but the PCR and ELISA tests have higher sensitivity. Prevention of leptospirosis in dogs can be done by vaccination, routine disinfection of dog house and preventing dogs from direct contact with reservoir animals such as rats